Answer:
x=-6
Step-by-step explanation:
use distributive property on the () and times x and 1 by three
then you subtract 6 from both sides
then subtract three from both sides
then divide both sides by 3
your work would look like this:
3(x+1)+6=-9
3x+3+6=-9
3x+3=-15
3x=-18
x=-6
Hope this helps!
Answer:
-(4,-3)
Step-by-step explanation:
You need to find the slope from point o to b, and then multiply it three times to get to b prime.
Answer:
The equation has no solution.
Step-by-step explanation:
Hi there!
First, let´s write the equation:
(√x + 3) + 6 = 3
To solve the equation, let´s subtract 6 to both sides of the equation:
√x + 3 = -3
subtract 3 to both sides of the equation:
√x = -6 (the square root of any number can´t be negative, but let´s solve it anyway and then check the solution).
Square both sides of the equation:
x = 36
Now, let´s check the solution:
(√x + 3) + 6 = 3
x = 36
(√36 + 3) + 6 = 3
(6 + 3) + 6 = 3
9 + 6 = 3
15 ≠ 3
Then, the equation has no solution.
Have a nice day!
Answer:
1830 sickers, 140.8 sticker sheets left
Step-by-step explanation:
13*203 = 2639
2639-809=1830
Using the Pythagorean triples, one side is 3 units long, one side is 4 units long, and one side is 5 units long. To find the area of a right triangle, multiply length times width. Then divide total by two.
So,
(3•4)/2= 6 units
After scaling units, you should get 24 units.